Medium-term variability of blood pressure and potential underdiagnosis of hypertension in patients with previous transient ischemic attack or minor stroke. - Cuffe, R; Howard, S; Algra, A; Warlow, C; Rothwell, P (2006)
BACKGROUND AND PURPOSE: Blood pressure (BP) is a major risk factor for stroke. However, the variability of systolic and diastolic BP (SBP and DBP) means that single measurements do not provide a reliable measure of usual BP. Although 24-hour ambulatory BP monitoring can correct for the effects of short-term variation, there is also important medium-term variability. The extent of medium-term variability in BP is most marked in patients with a previous transient ischemic attack (TIA) or stroke. We studied the potential impact of this variability on the likely recognition of hypertension. METHODS: We analyzed multiple repeated measurements of BP in 3 large cohorts with a TIA or minor stroke: the UK-TIA trial (n=2098), the Dutch TIA trial (n=2953), and the European Carotid Surgery Trial (ECST; n=2646). Regression dilution ratios and coefficients of variation were calculated for SBP and DBP from baseline and repeated measurements during the subsequent 12 months. Categorization based on single baseline measurements was also compared with categorization based on the subsequent "usual" BP. RESULTS: The correlation between measurements of BP at baseline and 3 to 5 months later was poor (R(2) from 0.17 to 0.31 for SBP and from 0.10 to 0.20 for DBP). Categorization of patients by baseline values resulted in substantial misclassification in relation to usual BP. For example, of patients with an SBP <140 mm Hg at baseline, the percentage with a usual SBP >or=140 mm Hg was 31.6% in the UK-TIA trial, 48.2% in the Dutch TIA trial, and 57.7% in the ECST. At least 3 consecutive measurements of SBP <120 mm Hg were required to be >90% certain that subsequent usual SBP would not be >or=140 mm Hg. CONCLUSIONS: Given the greater medium-term variability of BP in patients with a previous TIA or stroke than in the general population, single measurements of "normal" or "low" BP will substantially underestimate the true prevalence of hypertension.